Impact of high coverage of monovalent human rotavirus vaccine on Emergency Department presentations for rotavirus gastroenteritis. Issue 14 (30th March 2015) - Davey, Heather M.; Muscatello, David J.; Wood, James G.; Snelling, Thomas L.; Ferson, Mark J.; Macartney, Kristine K.
Highlights: Population study of RV1 vaccine program on non-admitted ED presentations in children. Demonstrated 55% decline in rotavirus-attributable, non-admitted ED presentations. 77% reduction in number of rotavirus ED presentations in the fourth program year. Abstract: Introduction: Australia was one of the first countries to introduce nationally funded rotavirus vaccination. The program has had a substantial impact on both rotavirus and all-cause acute gastroenteritis (AGE) hospitalisations and rotavirus laboratory tests. Evidence for an impact on Emergency Department (ED) presentations is limited. This study assessed changes in ED presentations for rotavirus in children aged <5 years in New South Wales, Australia, following introduction of monovalent human rotavirus vaccine (RV1, Rotarix ®, GlaxoSmithKline Australia Pty Ltd., Victoria, Australia). Method: A time series analysis to examine trends in total non-admitted ED presentations for all-cause AGE and in the rotavirus-attributable fraction using data on rotavirus positive laboratory tests. Results: A decline in the rate of non-admitted ED presentations for all-cause AGE was observed for all ages, being most notable in 1 year old children. Compared with the pre-vaccination period, we estimated the average weekly rate was lower across the first 4.5 years of the program for both all-cause AGE (18.3%; 70.5 versus 57.5 per 100, 000 population) and rotavirus attributable (55.4%; 17.3 versus 7.7 per 100, 000 population) presentations. In the fourth year of the program, estimated annual rotavirus attributable presentations were 77% lower than the pre-vaccination annual mean (996 versus 4300 per year). Conclusion: The program was associated with a substantial decline in rotavirus attributable non-admitted AGE presentations to ED among children aged <5 years.